ASSIMILATING THE DIASPORA OF THE AMERICAS IN AUSTRALIA: AN INTERGENERATIONAL ANALYSIS. Issue 1 (1st January 2023) - Forrest, James; Kusek, Weronika
ABSTRACT: People from the Americas are a small, largely neglected part of Australia's immigrant population. Most came from middle-class backgrounds in the post-global economic restructuring era (post-mid-1970s), though a minority were working class. Five dimensions of their intergenerational assimilation are analyzed: educational attainment and occupational status; linguistic shift; identification as Australians; discrimination (racism); and, for Sydney, first to second generations spatial assimilation. While the first three dimensions conform to the classic assimilation model, intergenerational socioeconomic status shift and spatial dispersal do so only partially. Intergenerational patterns of educational attainment and occupations broadly correlate, but first through third generation shift among both North and Latin Americans is downwards toward national means. Second generation ancestry groups are more dispersed than the first, but only a minority into host-society districts; suggested reasons include superdiversity, age, income, and housing market factors.